Local probe of single phonon dynamics in warm ion crystals - A. Abdelrahman (Nature Portfolio, 2017)
An exhausting characterization of the coherence properties of quantum system becomes challenging with increasing system size. Here the authors demonstrate that phonon autocorrelation functions and quantum discord can be measured with local control, and validate it in a string of 42 trapped ions.